PWE-011 Radiofrequency ablation of symptomatic cervical inlet patch using a through the scope device - a pilot study. (22nd June 2015) - Dunn, JM; Sui, G; Angiannsah, A; Wong, T
Abstract : Introduction: The Cervical Inlet patch (CIP) is an area of heterotopic gastric mucosa at the proximal oesophagus, which can secrete both acid and mucus. Attributable symptoms include chronic globus sensation and sore throat. Previous studies have demonstrated improvement in symptoms following ablation with argon plasma coagulation. 1, 2 The aim of this study was to assess a novel through the scope Radiofrequency Ablation (RFA) catheter, that may be advantageous for this indication. Method: Ten patients with endoscopically and histologically proven CIP, and symptoms of globus or sore throat, were included in the study. All had laryngoscopy, high resolution manometry and 24-hour dual-channel pH/impedance studies prior to enrolment. An ablation protocol of 3 ablations at 12J/cm 2, without removal of coagulated tissue between ablations, was employed. Patients were discharged on twice daily proton pump inhibitor (PPI) for 6 weeks, and a follow up endoscopy was undertaken at 3 months. A maximum of 2 RFA sessions, 3 months apart, were allowed. A visual analogue score (VAS; 0–100) was completed at baseline, then at 6 weeks (on PPI), 3 months (off PPI), 6 months and 12 months after treatment. Wilcoxon test was used for statistical analysis. Results: The mean age was 56 years (+/- 3 years, SEM), 60% male, 80% Causcasian. Barrett's oesophagus was present in 50%. Mean number of CIP was 2 (range, 1–4) with a median surface area of 2 cm 2 (range, 0.5–14cm 2 ). After a median of 2 RFA sessions, 80% achieved complete endoscopic and histological resolution (CR-IP), with >90% visual resolution for remainder. Globus, sore throat and cough were significantly improved from baseline (p < 0.05) (Table 1 ). There were no strictures or buried glands identified at follow up. Conclusion: This prospective pilot study demonstrates that RFA using the Barrx TM Channel Catheter is safe and effective for treating patients with symptoms of chronic globus sensation, secondary to cervical inlet patch. Disclosure of interest: J. Dunn Grant/Research Support from: Covidien GI Solutions, G. Sui: None Declared, A. Angiannsah: None Declared, T. Wong: None Declared. References: Meining A et al . Argon plasma ablation of gastric inlet patches in the cervical esophagus may alleviate globus sensation: a pilot trial. Endosc. 2006;38:566–570 Bajbouj M et al . Argon plasma coagulation of cervical heterotopic gastric mucosa as an alternative treatment for globus sensations. Gastroenterol. 2009;137:440–444